Spies, Patriots, and Traitors : American Intelligence in the Revolutionary War - Daigler, Kenneth A. (Book collections on Project MUSE., 2014)
Students and enthusiasts of American history are familiar with the Revolutionary War spies Nathan Hale and Benedict Arnold, but few studies have closely examined the wider intelligence efforts that enabled the colonies to gain their independence. Spies, Patriots, and Traitors provides readers with a fascinating, well-documented, and highly readable account of American intelligence activities during the era of the Revolutionary War, from 1765 to 1783, while describing the intelligence sources and methods used and how our Founding Fathers learned and practiced their intelligence role. The author.